The Android-Learned Media Learning Media With Health Material For Students of Class X (Department of Physical Education, Sport, Health and Recreation, 2017)
Seeing the potential of untapped learning media. Creativity of teachers to create learning media not only for solving problems, but also exploit the potential that exists. Therefore the author tries to design an Android-based program to improve learning experience of Physical Education, Sport and Health to be more interesting. Using Pre test and Post test method in trial scale. The results showed that, (1) the results of media expert and health expert validation showed 80.475% in the â€œexcellentâ€ category and small-scale trials showed an average of 54.114 results in pre test and 79.2 in the post test. (2) The results of data analysis on large-scale trials in 3 schools showed 52,867 results in the test and increased to 75.2754 in the post test. (3) The studentsâ€™ assessment on the product was 77.091% or in the â€œgoodâ€ category and the assessment of the learning expert was 89, 5% in the category of â€œvery good.â€ Learning media product of Physical Education, Health and Sport in Android-based named APPJOK with focused on subject types of foods and beverages that are beneficial to the health of growth and development can be practiced to the subject of the trial.